104th Fresno County Bar Association Annual Bar Banquet-TorNino's - Watkins, Howard::::::::: (1986)
In-coming Fresno County Bar Association President Howard Watkins presenting clock thank you gift to out-going Fresno County Bar Association President Judy Soley; William J. Smith and Dana French at head table